Influence of Marketing Expenses on the Profitability of the Listed Manufacturing Companies in Tanzania - Kisyeri , Dickson Matiko; Kira, Alex Reuben (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
In recent decades, marketing expenses have been one of the subjects that have taken much attention internationally due to the influence it has on the day-to-day business activities of different business companies. Several studies have been done on the relationship between marketing expenses and business companies’ profitability globally. However, there are limited studies that used DuPont analysis to examine the responding variable (profitability). To bridge this gap, this study examined the influence of marketing expenses on the profitability of listed manufacturing companies in Tanzania guided by the marketing mix theory. The study used an explanatory research design whereby all data for the response variables were collected from the financial reports of the six listed manufacturing companies. This study further used 84 observations or cross-sectionals from a population of six LMCs. Descriptive and correlation analysis and pooled OLS were used for data analysis with a help of EViews. The census as a sampling technique was used to consider all 6 LMCs. The results have indicated that marketing expenses have a negative influence on the profitability explained by DuPont. This implies that if companies want to successfully increase their profitability, then they must relatively reduce their spending on marketing their products.